Macrobrachium hungi, a new freshwater palaemonid prawn (Decapoda: Caridea: Palaemonidae) from the Tonle Sap Great Lake of Cambodia - van Xuan, Nguyen (Zootaxa, 2012)
A new species of the genus Macrobrachium, M. hungi was collected in theTonléSap Great Lake of Cambodia. The adultmales of this species show a close resemblance to Macrobrachium saigonense Xuân 2006, but they are larger, the rostrumis longer, distally directed upwards or not, with more numerous dorsal and ventral teeth; the tubercles on both sides of thecutting edge on the distal portion of the movable finger are vestigial or crescent shape and less prominent than those of M. saigonense. Notes on economic importance and its habitat which differs from M. saigonense are briefly provided.